Effect of megarectum on postoperative defecation of female patients with congenital rectovestibular fistula or rectoperineal fistula - Liu, Chunxiang; Wang, Song; Dai, Jinyu; Li, Jian; Wu, Xiaoxia; Liu, Yong; Yao, Zhiwei; Ma, Lushun; Sun, Xiaobing; Sun, Daqing (Frontiers in Pediatrics, 2023)
Background: To assess the effect of megarectum on postoperative defecation of female patients with congenital rectovestibular fistula or rectoperineal fistula. Methods: From March 2013 to February 2021, 74 female patients with congenital rectovestibular fistula or rectoperineal fistula were treated. The age of patients ranged from 3 months to 1 year. Barium enema and spinal cord MRI were performed in all children. 4 patients were removed from the study because of spinal cord and sacral agenesis. Finally,70 patients underwent one-stage anterior sagittal anorectoplasty(ASARP).Anal endoscopy and anorectal pressure measurement were performed 1 year after surgery. All patients were divided into two groups depending on the presence of megarectum (+) and (-) and observed for constipation and anal sphincter function. Results: 16 patients (4 months to 1 year) were complicated with megarectum, and 54 patients (3 months to 9 months) were without megarectum. The incision infection was seen in 3 patients. All patients were followed up for 1 year to 5 years. Fecal soiling was seen in 2 patients and constipation in 14 patients. Among 16 patients with megarectum, soiling was seen in 1 patient and the constipation in 12 patients.Among 54 patients without megarectum, soiling was seen in 1 patient and constipation in 2 patients.There was a significant difference in the incidence of postoperative constipation between the two groups (megarectum (+) 75% vs megarectum (-) 3.7% (P < 0.05)).However, there was no significant difference in the score of anal sphincters between the two groups (P < 0.05). And there was no significant difference in anal resting pressure (P = 0.49) and length of anal high pressure area (P = 0.76). 7 patients with constipation and megarectum acquired normal anal function after the dilated rectum was resected. Conclusion: Megarectum increases the possibility of difficult postoperative defecation in the patients with congenital rectovestibular fistula or rectoperineal fistula.However, constipation was not associated with ASARP postoperative effects on sphincter function. Resection of megarectum is helpful to the improvement of constipation.